2020
DOI: 10.1097/ajp.0000000000000818
|View full text |Cite
|
Sign up to set email alerts
|

Pain-related Self-efficacy Among People With Back Pain

Abstract: Background: Before an intervention can be implemented to improve pain-related self-efficacy, assessment is required. The aim of the present study was to provide a systematic review on which self-efficacy scales are being used among patients with back pain and to evaluate their psychometric properties. Methods: A systematic search was executed in January 2019 and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2009 checklist served… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…Pain self-efficacy refers to a patient’s confidence in his or her ability to tolerate pain and perform daily activities in spite of it. 20 , 21 A growing body of research has demonstrated that pain self-efficacy can predict mental and physical health. 22 , 23 Patients with chronic pain who have higher self-efficacy levels are more likely to perform health-related behaviors to alleviate the pain, which in turn leads to lower psychological stress and higher QOL.…”
Section: Introductionmentioning
confidence: 99%
“…Pain self-efficacy refers to a patient’s confidence in his or her ability to tolerate pain and perform daily activities in spite of it. 20 , 21 A growing body of research has demonstrated that pain self-efficacy can predict mental and physical health. 22 , 23 Patients with chronic pain who have higher self-efficacy levels are more likely to perform health-related behaviors to alleviate the pain, which in turn leads to lower psychological stress and higher QOL.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a 2020 systematic review by Vergeld et al, 47 which included 47 studies (14 of them reporting on the PSEQ-10), assessed psychometric properties of the PSEQ-10 when used with a population with LBP. They reported excellent internal consistency, with Cronbach alpha ranging from 0.88 to 0.94 and excellent test–retest reliability with ICCs ranging from 0.82 to 0.92.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 47 The number of items in these scales varies from 8 to 33 items, leading to a variable response burden (completion times). 47 Among all self-efficacy questionnaires, the PSEQ is the most frequently used in clinical setting for MSK disorders. 15 , 36 , 47 According to a Delphi study, it is the preferred clinician tool to assess pain-related self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations